Preglacial and Interglacial Environments of Banks Island: Pollen and Macrofossils from Duck Hawk Bluffs and Related Sites - Matthews Jr., John; Mott, Robert; Vincent, Jean-Serge (Géographie physique et Quaternaire, 1986)
ABSTRACTSediments ranging in age from Tertiary to Late Quaternary are exposed at Duck Hawk Bluffs near Sachs Harbour on Banks Island (NWT). Fossil pollen and macrofossils of plants and arthropods from various nonglacial sediments at Duck Hawk Bluffs and related sites on Banks and Victoria islands make it possible to infer some of the climatic/biotic changes during that time span. At the time of deposition of the Miocene-Pliocene Beaufort Formation, southern Banks Island supported a rich coniferous forest, containing several species of conifers and various hardwoods. An upper member of the Beaufort Fm. is characterized by a more depauperate coniferous forest assemblage, yet still contains plants now foreign to the entire NWT. The late Tertiary/early Quaternary Worth Point Formation was deposited when larch-dominated forest-tundra characterized southern Banks Island. Larch may have grown on the island during the following Morgan Bluffs Interglaciation (>730 ka), but in other respects the flora and fauna of that time seem to have been low Arctic in character. Similar conditions existed during the Cape Collinson Interglaciation ( = Sangamon), though by that time, coniferous trees had definitely disappeared from the island.